1989
DOI: 10.1016/0014-5793(89)81380-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis in P‐glycoprotein‐overexpressing human tumor cell lines Effects of resistance‐modifying agents

Abstract: We show that drugs, such as verapamil, which reverse multidrug resistance (MDR), in P-glycoprotein-overexpressing tumor cells, increased the rate of lactate production in four human MDR cell lines, but not in the parent, sensitive cell lines. The effect on glycolytic rate was maximal at a medium concentration of 2 PM verapamil. The glycolytic rate in sensitive (A2780) and MDR (278wD) cells showed the same pH dependence, but the effect of verapamil was seen only in 2780AD cells at all pH values investigated (6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 33 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…Therefore, a subsequent increase in cellular doxorubicin concentration by indomethacin may have partly played a role. Other mechanisms by which indomethacin might induce apoptosis are increased glutathione extrusion mediated by MRP1 (Trompier et al, 2004) or increased ATP consumption by MRP1 ATPase activity in analogy to the observed verapamil-induced ATP consumption in P-glycoprotein-overexpressing cells (Broxterman et al, 1989).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a subsequent increase in cellular doxorubicin concentration by indomethacin may have partly played a role. Other mechanisms by which indomethacin might induce apoptosis are increased glutathione extrusion mediated by MRP1 (Trompier et al, 2004) or increased ATP consumption by MRP1 ATPase activity in analogy to the observed verapamil-induced ATP consumption in P-glycoprotein-overexpressing cells (Broxterman et al, 1989).…”
Section: Discussionmentioning
confidence: 95%
“…Another example is the natural product Austocystin D, which possesses increased toxicity against some MDR cell lines as a result of increased activation by cytochrome P450 [75]. Increased sensitivity of MDR cells to the antimetabolite 2-deoxy-dglucose, the electron transport chain inhibitors rotenone and antimycin A [71,76,77] as well as certain P-gp-substrates [72,[78][79][80] were explained by the ATP depleting effect of the transporter. According to this model, increased glycolysis compensates for the higher energy demand created by the "futile cycling" of the transporter [79,81,82], but the oxidative stress associated with oxidative phosphorylation ultimately results in the selective apoptosis of MDR cells [83].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…One type of MDR is due to the overexpression of plasma membrane drug transporters, which act as ATP-dependent drug efflux pumps, resulting in lower intracellular drug concentrations and, hence, in drug resistance [1,3]. Hitherto, two different plasma membrane drug transporters have been cloned, namely the MDR1 encoded P-glycoprotein (Pgp) [4] and the recently discovered multidrug resistance protein (MRP) [5].…”
Section: Introductionmentioning
confidence: 99%